Impact : how rocks from space led to life, culture, and Donkey Kong - Brennecka, Greg (William Morrow, an imprint of HarperCollins Publishers, 2022)
A noted meteoriticist shows how meteorites have helped build our planet and influenced humanity since the start of civilization.